The Contribution of Self-Regulated Learning, Self-Awareness, and Spiritual Intelligence to Academic Achievement - Yuzarion; Diponegoro, Akhmad Muhammad; Prasetya, Akhmad Fajar; Taufikurrahman, Asvian; Isma, Afdila Ilham; Anari, Irfan (Universitas Islam Indonesia, 2024)
This research was prompted by the low academic achievement of students. This research aimed to determine the contribution of self-regulated learning, self-awareness, and spiritual intelligence using an ex post facto quantitative method. The population comprised 170 students from Vocational High School Muhammadiyah X in Yogyakarta City, with 81 selected using cluster random sampling. Data were systematically collected through the utilization of instruments designed to assess self-regulated learning, self awareness, and spiritual intelligence. Additionally, academic achievement data were acquired from Semester Final Examination scores. The results showed that self-regulated learning, self awareness, and spiritual intelligence made a highly significant contribution to academic achievement Moreover, the combined influence of self-regulated learning, self-awareness, and spiritual intelligence also significantly contributed to the variable.